Análise hidrossedimentológica e geoquímica dos ambientes aluviais da bacia riacho do tigre, semiárido paraibano - Silva, Adonai Felipe Pereira de Lima (2019)
The northeastern region of Brazil has historically been affected by the recurrent effects of prolonged droughts, compromising the socioeconomic development of dryland populations. The challenge of water management becomes more complicated when it comes to a semi-arid river environment, due to irregular rainfall and the absence of perennial watercourses. The exploitation of alluvial aquifers is an alternative to overcome the water scarcity. In this perspective, the objective of this work is to perform a hydrosedimentological analysis of the alluvial deposits of the Tigre - PB basin and its geochemical characteristics, as well as to evaluate the quality of the water retained in the alluvial aquifers through the shallow wells. In order to reach the proposed ends, the sedimentological analyzes of granulometry, chemical analyzes from the X-Ray Fluorescence, mineralogical analyzes from the X-ray Diffraction and water quality assessment were carried out utilizing measurements made with a multiparameter probe in the wells alluvial. There were five sections analyzed in total. The results revealed that the information obtained from each section allowed establishing a relationship between natural and anthropic conditions with their own sedimentological and hydrological characteristics. With the sedimentological information obtained, it was possible to define that stretches 1 and 2 are in a group with a higher percentage of gravel and with intermediate values of clay and silt. The stretches 3 and 4 are in a group with a predominance of sand, and low percentage of silt, clay and gravel; and section 5 is alone in a group with a higher percentage of silt the clay in relation to the others, with alternation of hydrodynamics between low, moderate, high and very high. The FRX techniques allowed the identification of 13 oxides in total, however in section 3, the diversity of elements is the largest, also being the only section with the presence of heavy metal (Cr). The XRD techniques allowed the identification of the minerals in all the stretches, being stretch 1 and stretch three the points with greater mineralogical diversity, all coinciding with the geological and lithological characteristics of the research area. The quality of the water in the wells showed to be variable according to the climatological season, referring to August (post-rainy period), November (dry period) and March (rainy season), whose analyzed parameters values (pH, total dissolved solids, conductivity, salinity, etc.) indicated better quality in the rainy season. The set of information obtained with the different analyzes allowed to create typologies of classification for the deposits analyzed: Sandy deposits in Pediment Area, Sandy deposits of Bedside in Pediment Area and Sandy deposits of Headboard in Top Plane. The information generated in this research is of paramount importance for the integration of environmental planning in drylands, whose water deficit requires a better use and use of groundwater resources, especially of wells that collect water from free aquifers.